UPTAKE AND OUTCOMES OF MILD OVARIAN STIMULATION FOR IN-VITRO FERTILIZATION IN AFRICA: A SYSTEMATIC REVIEW (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Introduction: Assisted Reproductive Technology (ART) is beyond the economic reach of most of those inflicted by infertility in Africa. Uptake of low-cost in-vitro fertilization (LCIVF) may improve financial access of patients to advanced fertility care.Methodology: Systematic review of open-access full articles published in English from January 2000 to May 2023. Articles were sourced via PubMed, Medline, Embase and Google Scholar databases on June 1st 2023. Search keywords used were “Mild stimulation” OR “Low-cost IVF” AND “Africa”.Ethics: This project was subjected to Ethics review by the University of South Wales Ethics review Committee.Results: 5 publications included out of 647 results. These were historical reports in contextualized narrative reviews with no statistics provided. Because of this, only qualitative synthesis was undertaken, and meta-analysis was not possible due to lack of statistics for comparison. Published results indicated significant financial restriction of access and no objective demonstration of actual uptake and outcomes of mild ovarian stimulation in Africa.Discussion: There was no actual open-access published evidence regarding uptake of mild stimulation for low-cost IVF in Africa. If there is such material, it is not available to those that would actually need the information to inform providers’ practice or patient choices. This is the case despite growing evidence of increasing utility of LCIVF outside Africa. Uptake of LCIVF may potentially ameliorate financial restrictions of access to ART in Africa.